Inverse Problem with Free Boundary for Heat Equation - Ivanchov, N. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We establish conditions for the existence and uniqueness of a solution of the inverse problem for a one-dimensional heat equation with unknown time-dependent leading coefficient in the case where a part of the boundary of the domain is unknown.